Exploring the status of African Women in the South African Labour Market 1995-2004 - Ntuli, Miracle (School of Economics, 2014)
For so long, black South African women have suffered from cultural and legalised discrimination. This gradually marginalised them from mainstream economic activities. Since the demise of Apartheid in 1994, the new government introduced corrective measures to improve the status of women in the labour market. For example, new legal provisions were enacted while international laws were also embraced. This demonstrated the government's commitment to achieve equality between men and women in the labour market and society at large. Given that more than ten years have passed since the inception of such enabling policies, it is reasonable to assume that remarkable strides were made in improving the status of African women in the job market. Therefore, this thesis aims to investigate whether the position of African women in the labour market has improved or not over the period 1995-2004. This audit is important for poverty eradication initiatives. Enhancing the status of women in the labour market is one vehicle through which poverty can be eradicated in the economy. The research focuses on three central areas. Firstly, the study explores the determinants of African women's labour force participation in 1995, 1999 and 2004. It uses logit models and the Even and Macpherson (1990 1993) decomposition. On the basis of this methodology, the study finds that for each of the three cross sections, education was the major correlate followed by non-labour income, marital status, geographical location and fertility. Furthermore, the increase in female labour force participation between 1995 and 2004 was mainly due to differences in coefficients/behavioural response than to a change in characteristics. The latter was especially due to behavioural response to education and age. However, these changes did not go far enough to make an improvement on the status of African women in the labour market. Specifically, the increase in female labour force participation was weighed down by some labour market inequalities associated with the trend like gender pay gaps. Secondly, gender wage differentials are scrutinized across the entire wage distribution in 1995, 1999 and 2004. The analysis utilises quantile regression estimation and counterfactual decomposition methods. This framework provides different estimates of the 'discrimination' coefficient across the wage distribution. In particular, it reveals that the gender gaps are wider at the bottom than at the top of the wage distributions. To add on, the research finds that the unexplained components of the gender pay gaps 'discrimination' did not substantially decline across the wage distributions between 1995 and 2004. Instead, the unexplained gaps slightly declined in the lower quantiles while increasing at the top end of the distributions. This probably indicates the persistence of substantial discrimination in the South African labour market, and that the incidence is more severe at the bottom than at the top of the wage distributions. However, rather than being a causal factor, this discrimination could be a symptom of the underlying problems. One of the possible causes is the low membership and hence representation of women in v decision making bodies such as trade unions. This invited a consideration of the gender differences in union membership. Finally, the research seeks to establish the nature and extent of the gender differences in trade union membership. It hypothesises that the gaps are either due to family loyalty, differences in union related characteristics or to discrimination. The analysis makes recourse to the Even and Macpherson (1990 1993) decomposition. The study finds that the gender gaps for 1995 and 2004 were mostly due to the unexplained components of the gender gaps/behavioural response, especially, differences in responses to family attachment related variables: marriage, occupations and industries. These outcomes sometimes show that most women spend most of their time carrying out domestic chores when compared to men. This suggests the persistence of patriarchal attitudes in society. Overall, our findings suggest that the changes in the status of African women in the post-Apartheid labour market were mainly due to responses to the constitution induced transformation rather than to a change in labour market characteristics. Nonetheless, this raises a question as to why, on the one hand, there were considerable shifts in labour force participation and on the other, there were negligible changes in unionism and pay gaps, yet all are explained by differences in coefficients. Therefore, we have suggested that the paradox resulted from massive changes in women's expectations about their involvement in paid work which are in concurrence with slowly changing social expectations about the role and place of women in the home and in the greater society. Clearly, women suffer from the work-family conflicts which compromise their advancement in the labour market. Also, it seems employers have not yet changed their discriminatory perceptions about women despite the presence of anti-discrimination legislation. The negative effect of this is to some extent an artefact of the persistence of patriarchal attitudes which continue to give women less voice in the labour market and in the society at large. Thus, we conclude that African women's de facto situation at the bottom of the hierarchy in the South African labour market is not mitigated by their de jure equality status. From these findings we speculate that the retention of patriarchy underlies the virtual restriction of an improvement in African women's labour market status. Therefore, we suggest that there is an urgent need for reforming gender roles at the societal level so that they exist on a more equal foundation and provide the basis for free and fair development of African women in the labour market.